Pengaruh Modal Sosial Terhadap Permintaan Pangan Rumahtangga Tani di Provinsi Riau - Fahmi Wiryamarta Kifli; Jangkung H. Mulyo; Dwidjono Hadi Darwanto; Slamet Hartono (Jurnal Manajemen & Agribisnis, 2017)
The objectives of this study were to analyze the factors that affected the food demand by the farmer households in Riau Province and to analyze how social capital is influential toward this demand. The research was conducted in four districts with different characteristics including Indragiri Hilir and Rokan Hilir as the regional representation with high activities of food crops, while Kampar and Rokan Hulu as the regional representation to the medium activities of food crops. The study was conducted in the two-survey period. The first survey was carried out in Indragiri Hilir and Kampar Regencies with the number of households as many as 114 in 2013, and the second survey was conducted in Rokan Hilir and Rokan Hulu Regencies with the number of households of 96 farm households in 2014 so that the total samples reached 210 farm households 4. The sampling was carried out randomly. The function of farmer household food demand was analyzed using the model of farm household and was estimated by Ordinary Least Sguare (OLS). The results showed that the variables of age of the household head, education level of farmers, number of household members, household income, and social capital had positive effects on the food demand for the farmer households while the variables of the prices of rice, potatoes, eggs, chicken meat, fish, and cooking oil had negative effects on the food demand for the farmer households in Riau Province. Furthermore, the results showed that social capital in the society built on the four (4) aspects, namely, trust, social networks within the support structure, norms and values, and levels of participation in the organization has contributed positively to food security of the farmers in Riau Province. Therefore, the community needs to build a high social capital, cooperation and mutual assistance, especially for the environment that has difficulties in finding food.Keywords: social capital, demand, food, farm household, food security